Impact of par-baking and packaging on the microbial quality of par-baked wheat and sourdough bread. (September 2018) - Debonne, Els; Van Bockstaele, Filip; Van Driessche, Manon; De Leyn, Ingrid; Eeckhout, Mia; Devlieghere, Frank
Abstract: The impact of processing conditions on the microbial quality of par-baked wheat and sourdough bread was investigated. Processing conditions included par-baking time (8 and 13 min), temperature (150 and 200 °C), amount of steam (200 and 600 mL), and packaging (air and modified atmosphere (MA)). Total anaerobic mesophilic plate counts, moulds and yeasts and spore-forming bacteria, together with pH and aw of the par-baked breads were evaluated. Data were used to make predictive models showing the impact of the main effects and their interactions. Sourdough addition could extend the time of acceptable bread quality based on the anaerobic counts from 8 to more than 13 days. Visual growth of moulds and yeasts (presence/absence of single spots) was most efficiently suppressed by the combination of MA-packaging and the highest baking temperature and time. Microbiological analysis of moulds and yeasts however, showed that again sourdough had the best preservation potential, followed by MA-packaging. This study showed that adjusting the par-baking conditions, bread composition and packaging can increase the shelf-life of par-baked bread in a natural way. Highlights: The water activity of par-baked bread was not influenced by steam during baking. L. sanfrancisce nsis was the most dominant lactic acid bacteria present in the sourdough. Kazachstania humilis was the most dominant yeast present in the sourdough. Anaerobic bacteria were reduced by sourdough and by increasing baking temperature. Mould and yeast spoilage was reduced by sourdough and MA-packaging.